Acceptability of internet-based cognitive behavioural therapy (i-CBT) for post-traumatic stress disorder (PTSD): a systematic review. Issue 1 (31st December 2019) - Simon, Natalie; McGillivray, Leah; Roberts, Neil P.; Barawi, Kali; Lewis, Catrin E.; Bisson, Jonathan I.
ABSTRACT: Background : Internet-delivered Cognitive Behavioural Therapy (i-CBT) offers potential as an alternative, accessible, clinically and cost-effective treatment for post-traumatic stress disorder (PTSD), but little is known about its acceptability. Objective : To review the available evidence to understand the acceptability of i-CBT for PTSD. Method : We undertook a mixed-methods systematic review according to Cochrane Collaboration Guidelines, of randomised controlled trials (RCTs) of i-CBT for adults with PTSD. We examined included studies for measures of acceptability, and possible proxy indicators of acceptability, including dropout rates, which were meta-analysed as risk ratios (RRs). Results : Ten studies with 720 participants were included. We found i-CBT to be acceptable according to specific acceptability measures, and suggestions for acceptability according to some proxy measures of i-CBT programme usage. There was, however, evidence of greater dropout from i-CBT than waitlist (RR 1.39, CI 1.03–1.88; 8 studies; participants = 585) and no evidence of a difference in dropout between i-CBT and i-non-CBT (RR 2.14, CI 0.97–4.73; participants = 132; 2 studies). Conclusion : i-CBT appears a potentially acceptable intervention for adults with PTSD. We identified clinical and research questions, including the status of proxy indicators, and call for standardised, consistent treatment acceptability measurement. HIGHLIGHTS: A review of acceptability of internet-delivered CBT (i-CBT) for PTSD. I-CBT is a potentially acceptable psychological treatment for PTSD. Small number of studies limits generalisability of findings. Standardised, consistent acceptability measurement is needed.